THE USE OF FILTRATION MATERIALS TO REMOVE AMMONIA FROM WATER - Hanusová, Anna (GeoScience Engineering, 2014)
Ammonia nitrogen is the primary product of the decomposition of plant and animal organic nitrogenous materials. Ammonium salts are part of some nitrogen fertilizers and are getting into ground and surface waters from agricultural areas. Secondary ammonium compounds can be formed directly in waters by reducing nitrates. This article is focused just on removing ammonia from drinking water, while the current research emphasizes the use of natural materials, especially for the removal of inorganic contaminants from water. The aim of this work consists in verifying the possibility of using natural filter materials - zeolites in ammonia removal and other filter materials, verify sorption (ion exchange) properties and efficiency of available types of materials under laboratory conditions.